Risk of human papillomavirus infection and cervical intraepithelial lesions in Chinese renal transplant recipients - Ming Chen; Qiulin Cui; Meilian Chen; Meng Xia; Duo Liu; Peisong Chen; Changxi Wang; Mian He (Frontiers in Oncology, 2022)
ObjectiveWhile human papillomavirus (HPV) infection in women is associated with cervical intraepithelial neoplasia and cervical cancer, HPV testing is not often performed in routine practice for renal transplantation patients. The genotype-specific prevalence of HPV and risk factors for HPV infection are still unclear.MethodsFrom 2010 to 2020, patients receiving renal transplantation surgery (referred to as RTRs), who had been screened for HPV infection one year after transplantation were enrolled. A comparison cohort of four age- and marital status-matched healthy individuals was selected for RTRs. The clinical characteristics and cervical screening results of RTRs were analyzed.ResultsOur study included 196 female renal transplant recipients (RTRs), none of whom had been vaccinated against HPV. Overall high-risk HPV (hrHPV) infection and abnormal cytology rates in the RTR group were 23.5% and 20.9%, respectively. The odds ratios of hrHPV infection and cervical intraepithelial neoplasia grade 2+ in RTRs vs. non-RTRs were 3.033 (95% CI, 2.013-4.568) and 3.628 (95% CI, 1.863-7.067), respectively. The prevalence of HPV16 in RTRs was much higher (30.4% vs. 8.3%, P=0.002). The multi-infection rate was much higher in HPV-infected RTRs (23.9% vs. 1.14%, P<0.001). The only risk factor for hrHPV infection was the duration of immunosuppression, which increased with time.ConclusionRTRs had significantly higher HPV infection rates and increased risks of HPV-related cervical premalignancies and cancers due to the immunosuppressed state. The duration of immunosuppression is a risk factor for transplant recipients. Female RTRs may benefit from more frequent cervical cancer screening after renal transplantation than healthy women. Prospective research on HPV infection dynamics in RTRs and optimal screening methods should be further explored in the future.